β2-Microglobulin: A Powerful Biomarker for Chronic Kidney Disease Progression - Yanuar Surya Saputra Poedjijo; Drajad Priyono; Deka Viotra; Harun, Harnavi (HM Publisher, 2025)
Background: Chronic kidney disease (CKD) is a global health concern with increasing prevalence. Early detection and accurate prognosis are crucial for effective management. β2-microglobulin (β2M) has emerged as a promising biomarker in CKD, but its prognostic value requires further evaluation. This meta-analysis aimed to comprehensively assess the association between β2M and CKD progression. Methods: A systematic search of PubMed, Embase, and Cochrane Library was conducted for studies published between 2013 and 2024 investigating the relationship between β2M and CKD progression. Studies were included if they reported hazard ratios (HRs) with 95% confidence intervals (CIs) for the association between β2M levels and renal endpoints (e.g., end-stage renal disease [ESRD], doubling of serum creatinine, or a decline in estimated glomerular filtration rate [eGFR]). A random-effects model was used to pool the HRs. Results: Six eligible studies involving 5,420 participants were included. The pooled analysis demonstrated a significant association between elevated β2M levels and increased risk of CKD progression (HR = 2.15; 95% CI: 1.78-2.59; p < 0.001). Subgroup analyses revealed that this association remained consistent across different CKD stages and underlying etiologies. Conclusion: Elevated β2M is a strong and independent predictor of CKD progression. Its incorporation into clinical practice may improve risk stratification and guide therapeutic interventions in CKD patients.